Analisis Kualitatif dan Kuantitatif Antioksidan Parang Romang: Qualitative and Quantitative Antioxidant Analysis of Parang Romang - Muhammad Ikhlas Arsul; Nurshalati Tahar; Afrisusnawati Rauf (Jurnal Sains dan Kesehatan, 2022)
Antioxidants can be found naturally in plants, animals, and microbes, or they can be produced chemically. The selection of plants to find the new bioactive compounds are carried out through ethnobotany and chemotaxonomic approaches. One plant that can be developed as an antioxidant is parang romang (Boehmeria virgata). This study aimed to identify an antioxidant activity on the roots, stems, leaves, and flowers of parang romang plant qualitatively and quantitatively. The parang romang plant used was obtained from Malino Regency, South Sulawesi. The roots, stems, leaves, and flowers were extracted using the reflux method and then concentrated using a rotary evaporator. Each part was analyzed for its chemical content and activity qualitatively and quantitatively. Qualitative analysis was carried out with sitroborat, folin ciocalteu, DPPH, FRAP, and CUPRAC reagen, while quantitative analysis was carried out by spectrophotometry using the DPPH method. The roots, stems, leaves, and flowers were detected to contain phenolic, and flavonoid compounds and have antioxidant activity based on qualitative analysis. The antioxidant activity of parts of the parang romang plant is classified as strong to very strong, with an AAI value of 1.5 - 4.54. All parts of the plant tested have antioxidant activity.